ANALISIS GERAK FREE THROW TERHADAP KEBERHASILAN MENEMBAK DI TIM BOLABASKET FIK UNIVERSITAS NEGERI MALANG - Abdulloh, Ido Nur; Saichudin, Saichudin; Merawati, Desiana (Jurnal Sport Science, 2016)
Abstract :Motion Analysis of Free Throw Shooting To Success In Basketball Team Nikken University of Malang is a research that aims to determine the success rate of motion free throw in basketball sport in terms of the principles of biomechanics. This research uses quantitative-qualitative research with descriptive analysis method. In his research, the author uses instruments such as: 1) the distance players, 2) angle of the foot, 3) arm angle, 4) corner throw, 5) The maximum height of the ball, 6) and the speed of the ball is aided also by software dartfish. The analysis shows that despite the resulting hand corner nearing 90 Â° can not fully be a reference ball can enter. This is because the factors that influence the speed of the ball more. Considered good ball speed when its value reaches 2.9 m / s or more. So the effect on ball speed level and also the maximum height that the ball can affect the effectiveness of the entry-level ball.Keywords :Motion Free Throw,Shooting success,Dartfish